Dinamika Historis Konstitusional, Sosial Politik, Kultural, Serta Konteks Kontemporer Penegakkan Hukum, Dan Pemberantasan Korupsi Dalam Pembangunan Negara Hukum Yang Berkeadilan - Eli Sabrifha (CV. SINAR HOWUHOWU, 2026)
This study examines the historical constitutional dynamics, socio-political and cultural dimensions, as well as the contemporary context of law enforcement and corruption eradication in the development of a just rule of law state in Indonesia. The study is motivated by the importance of the supremacy of law as the primary foundation for establishing democratic, transparent, and integrity-based governance. The research applies a normative juridical method through library research by analyzing legislation, legal theories, and relevant academic literature. Indonesia’s constitutional development reflects a close relationship between political system changes, public legal culture, and the challenges of globalization toward law enforcement practices. The findings reveal that law enforcement and corruption eradication continue to face significant challenges, including political intervention, weak institutional integrity, and low public legal awareness. From a cultural perspective, the success of corruption eradication depends not only on strong regulations but also on morality, public ethics, and community participation in monitoring government practices. Therefore, the development of a just rule of law state requires synergy between a democratic constitution, independent law enforcement, anti-corruption culture, and sustainable legal reform to create fair and accountable governance.